Spectral encounters: the Latin American immigrant and other ghosts of England - Delgado, Oscar (2020)
This novel and its critical companion express the unacknowledged presence of the Latin American immigrant in England in terms of the ghost. Penumbra is the story of Samuel, a Costa Rican immigrant settling in contemporary England, and narrates his encounters with literal and figurative ghosts. My research draws from the Derridean concept of hauntology and the critical approach developed from it to specify the challenges the ghost can pose to the dichotomies of presence and absence, as well as past and present. I map these challenges within the encounters of the Latin American immigrant with different cultural subjects in England to point out instances of Othering and postcolonial melancholia. What the novel depicts is a complex modern globalised England that tends to romanticise its Victorian past, that clings to certain aspects of this particular era. In Penumbra, these ideas filter through the everyday experiences and fantastical visions of a foreign narrator who struggles to reconciliate his confounded expectations with the reality of the country. This project has a microsociological focus. Its subject is a migrant individual adjusting to ghostliness in England, rather than Latin America as an ethnic group. The fiction explores the mechanisms of the Latin American protagonist for coping with such ghosts and emphasises the relevance of his anecdotical narrative for breaking it. My treatment of the spectre as a metaphor for the Latin American exposes the practices and everyday-life occurrences that make this subject invisible, voiceless, and liminal. This series of ghostly encounters pace the development of the main character, but what moves the plot forward is the protagonist’s awareness of his own ghostliness. The critical companion to the novel has four parts. The first one delineates the challenges hauntology poses to the concepts of presence and time, on which I base the rest of my analysis. I introduce two modalities of the ghost, the sensuous presence to which I connect the term ‘spectre’, and the symbolic modality which I identify with the term ‘ghost’. Part Two localises the hauntological argument of presence within the context of the Latin American immigrant in contemporary England in order to justify the characterisation of my protagonist. I examine the reasons for the inconspicuousness of the Latin American, looking at the historical relations between Europe and Central America, and more specifically between England and Costa Rica. I introduce my term of ghosting to refer to the practices that render the Latin American Other invisible. The central idea of Part Three is the challenge of hauntology to our concept of time, specifically, the solidity of the present. I analyse the impact of the returning past, not only on the foreign protagonist of Penumbra but also on the country as a whole. I concentrate most of my literary analysis on Part Four of the critical section. This last section focuses on the ghost as an instrument and subject of my creative practice. I study the themes of presence and time other authors have explored through a ghostly filter and compare them to my rendition. I locate my fiction in relation to other ghost literature. I conclude with the idea that both the sensuous and symbolic modalities of the ghost are complementary to each other and together make for a strong conceit of the invisibility of the Latin American immigrant in England.